Health and frailty among older spousal caregivers: an observational cohort study in Belgium - Potier, Florence (BMC Geriatr, 2018)
BACKGROUND: Among older couples, spouses are first in line to provide care, and they are key elements in the home support of dependent older persons. In this context, ensuring the health of these older spousal caregivers should be an important issue for all of the providers who care for older adults. The aim of this study was to longitudinally assess the health of older spousal caregivers considering frailty, nutrition, cognition, physical performance and mood disorders. METHODS: In this longitudinal, observational cohort study, participants were assessed at home in Wallonia, Belgium. At baseline, 82 community-dwelling spouses of older patients with cognitive deficits or functional impairment were assessed; 78 caregivers were assessed at follow-up (16 months). The clinical instruments used included Frailty Phenotype (Fried), the Mini Nutritional Assessment-short form (MNA-SF), Short Physical Performance Battery (SPPB), Geriatric Depression Scale (GDS-15), clock drawing test, medications, Zarit Burden Index (ZBI), and Caregiver Reaction Assessment (CRA). Biological assessments included plasma interleukin-6 (IL-6), ultrasensitive C-reactive protein (CRP), cortisol, albumin and insulin growth factor-1 (IGF-1). RESULTS: Among caregivers, 54% were women, and the mean age was 80 years. Among care-receivers, 83% had cognitive impairment. Caregivers were more likely to be in a pre-frail stage. In one-third of the caregivers, the frailty status worsened. Transitions were observed between each of the states, except from frail to robust. In contrast to frailty, items including nutrition, cognitive status, SPPB and mood assessments were stable over time, with approximately 70% of the caregivers not experiencing significant change at follow-up. Caregiver experiences assessed with the Zarit Burden Interview and CRA were relatively stable over 16 months. CONCLUSION: Many caregivers of geriatric patients are spouses who are old themselves. A failure in the health of the caregiver may anticipate an undesired care breakdown. Caregiver health and its determinants should be explored in future longitudinal studies that cover a longer time period. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12877-018-0980-3) contains supplementary material, which is available to authorized users.